Analisis Tingkat Kepatuhan Pajak Penghasilan pada Wajib Pajak Pelaku UMKM di Indonesia - Saraswati Saraswati; Mahmudi Mahmudi (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2023)
This research aims to analyze the effects of tax morality, perception of justice, trust in public authority, taxpayer awareness, understanding of tax procedures and understanding of tax regulations on tax compliance by taxpayer micro, small and medium enterprises (MSMEs) in Indonesia. Taxpayer compliance is a situation where taxpayers must fulfill and carry out all their tax duties. The sample of this research is taxpayer of micro, small and medium enterprises. This research used purposive sampling method, then obtained 155 taxpayers as respondents. IBM SPSS Statistics 26.0 was used to performed data analysis with multiple linear regression models. The results shows that tax morality, perception of justice, trust in public authority, taxpayer awareness, understanding of tax procedures and understanding of tax regulations have a positive and significant effect on MSMEs taxpayer compliance in Indonesia.